The Syllidae (Polychaetous Annelids) from Japan. II. Autolytinae. - Imajima, Minoru (Publications of the Seto Marine Biological Laboratory, 1966)
[Abstract of Parts I-V:] The Syllidae of Japan are named with 77 species and 7 subspecies in 20 genera, 5 subgenera and 4 subfamilies; 2 others in 2 genera are not determined specifically. One new genus, 1 new subgenus, 31 new species or subspecies and 5 new combinations are given. 21 species or subspecies are new to Japanese waters. One genus, Geminosyllis is erected from Syllinae and one new subgenus, Regulatus is named in Autolytus. 46 species or subspecies, 53.4%, are currently known only from Japan, 40 others are known also from other areas.
World Polychaeta Database (WPolyDb)